Improvement of crystallinity of GaN layers grown using Ga2O vapor synthesized from liquid Ga and H2O vapor. (4th April 2016) - Yamaguchi, Yohei; Taniyama, Yuuki; Takatsu, Hiroaki; Kitamoto, Akira; Imade, Mamoru; Yoshimura, Masashi; Isemura, Masashi; Mori, Yusuke
Abstract: Growth methods using Ga2 O vapor allow long-term growth of bulk GaN crystals. Ga2 O vapor is generated by the reduction of Ga2 O3 powder with H2 gas (Ga2 O3 –H2 process) or by the oxidation of liquid Ga with H2 O vapor (Ga–H2 O process). We investigated the dependence of the properties of grown GaN layers on the synthesis of Ga2 O. In the Ga–H2 O process, the polycrystal density and full width at half maximum (FWHM) GaN(0002) X-ray rocking curves (XRC) at a high growth rate were lower than those in the Ga2 O3 –H2 process, and a GaN layer with FWHM of 99 arcsec and growth rate of 216 µm/h was obtained. A low H2 O partial pressure in the growth zone improved crystallinity in the Ga–H2 O process, realized by the high efficiency of conversion from liquid Ga to Ga2 O vapor. We concluded that using Ga2 O vapor in the Ga–H2 O process has the potential for obtaining higher crystallinity with high growth rate.